Genetic variation and associations involving Fusarium head blight and deoxynivalenol accumulation in cultivated oat (Avena sativa L.). (20th July 2017) - Bjørnstad, Åsmund; He, Xinyao; Tekle, Selamawit; Klos, Kathy; Huang, Yung‐Fen; Tinker, Nicholas A.; Dong, Yanhong; Skinnes, Helge
Abstract: Resistance in oats ( Avena sativa L.) to Fusarium graminearum was phenotyped in 424 spring oat lines from North America and Scandinavia and genotyped with 2974 SNP markers. Fusarium head blight (FHB), deoxynivalenol (DON) content, days to flowering (DTF) and days to yellow maturity (DTM) were scored in field trials in 2011–12. Trials with phenotypic ranges from 1 to 30 ppm, and sufficient accuracy were obtained by an augmented design and spawn inoculation. Discriminant analysis–PCA identified the different gene pools, with overlaps corresponding to known pedigrees and germplasm exchanges. Structure was negligible and GWAS (genomewide association study) was done using mixed linear models in TASSEL or partial least‐squares regression (PLSR). PLSR allows simultaneous analyses of several phenotypes (environments and/or traits) and is a promising tool for GWAS in plants and should be tested in species with sequenced genomes. FHB was associated with phenology QTLs, due to very susceptible early lines from the Midwest. Lines with consistently low DON (and early heading) were identified. Six QTLs for DON were not associated with earliness, including three QTLs reported previously.